Galvanomagnetic properties of superconducting granules and grain boundaries in ceramic YBa₂Cu₃O₇₋δ high-temperature superconductor - Sukhareva, T.V. (Functional Materials, 2012)
he objective of the work is to reveal the contribution of superconductive granules and grain boundaries (weak links) in magnetoresistance p value of YBa₂Cu₃O₇₋δ granular high-temperature superconductor (HTS) at T < Tc. The current-voltage characteristics (CVCs) E(j)Hext=const of YBa₂Cu₃O₆.₉₅ ceramic samples were measured in (0 < Hext ≤≈ 500 Oe) magnetic fields. The CVCs E(j)Htrap =const of the samples magnetized in Htreat magnetic fields were measured at Hext = 0. Based on the CVCs, p(j)Hext=const, p(Hext)j=const and p(j)Htreat=const dependences were reestablished. The comparative analysis of p(j)Hext=const and p(Hext)j=const dependences indicates the magnetic field redistribution between grain boundaries and superconductive granules influence on transport and galvanomagnetic properties of granular HTS. The superconductive grain magnetoresistance pg was established to be significantly lower than pj value of Josephson medium.